Unraveling structure sensitivity in phenol hydrogenaton on Pd nanostructures - Haider, M. Ali; Seshadri, Sreedhala; Gupta, Shelaka; Khan, Tuhin; Prabhakaran, Vinod (253rd National Meeting of the American-Chemical-Society (ACS) on Advanced Materials, Technologies, Systems, and Processes, 2017)

Mechanistic insights into the pathways of phenol hydrogenation on Pd nanostructures - Porwa, Govind; Gupta, Shelaka; Sreedhala, S.; Elizabeth, Joes; Ithan, Tuhin Suvra; Haider, M. Ali; Vinod, C. P. (ACS Sustainable Chemistry & Engineering, 2019)
Product selectivity in aqueous phase phenol hydrogenation on well-defined supported Pd nanostructures (spheres, cubes, and octahedra) was studied using defined experiments and density functional theory (DFT) simulations. On Pd spheres and octahedra, the reaction initially showed high selectivity (in the first 3 h, at 363 K and 5 bar H-2 pressure) toward the partially hydrogenated product cyclohexanone. On prolonged operation (>20 h of reaction time), a shift in the product selectivity (up to 100%) toward the completely hydrogenated product cyclohexanol was observed on Pd spheres and octahedra. In contrast, the reaction on Pd cubes, which only had {100} facets, showed a high selectivity (similar to 90%) toward the product cyclohexanone even after 40 h, at the same reaction conditions. Since the {111} facets are expected to be the majority sites on a spherical particle, we attribute the selectivity trend observed on spherical Pd particles to be primarily controlled by the selectivity trend on the Pd{111} facets. This observation was further confirmed on performing the hydrogenation reaction on a mixture of Pd cube and Pd octahedron particles in a ratio of 25:75 (representing the site ratio of a spherical particle). DFT simulations provided a mechanistic insight into the reactivity of the two different facets ({100} and {111}) toward phenol hydrogenation. The calculations revealed that the selectivity significantly depended on the activation barriers involved in cyclohexanone hydrogenation on the Pd{111} facets (77 and 57 kJ/mol) as compared to those on the Pd{100} facets (97 and 101 kJ/mol).
Keywords: Cyclohexanol; cyclohexanone; facet-dependent reactivity; phenol hydrogenation

CuO as a reactive and reusable reagent for the hydrogenation of nitroarenes - Rajendran, K.; Pandurangan, N.; Vinod, C. P.; Khan, Tuhin S.; Gupta, Shelaka; Haider, M. Ali; Jagadeesan, D. (Applied Catalysis B-Environmental, 2021)
{Copper oxide (CuO) is used as a reusable solid reagent for hydrogenation of nitroarenes to aminoarenes. The use of CuO resulted in 100 % conversion of 2.9 mmol of nitrobenzene to aniline in 45 s at room temperature using hydrazine hydrate as the reducing agent. During the reaction, CuO is converted to inactive metallic Cu which can be regenerated to active CuO by thermal oxidation. DFT simulations indicated facile formation of oxygen vacancies (EO
Keywords: Copper vacancy; CuO; Hydrogenation; Nitroarene reduction; Oxygen defects; Reactive solids

Facet dependence for solvent-modulated proton-coupled electron transfer in furfural acetalization on Pd nanostructures - Porwal, Govind; Dandekar, Pallavi; Gorai, Twinkle; Khan, Tuhin Suvra; Haider, M. Ali; Gupta, Shelaka; Vinod, C. P. (Chemical Engineering Journal, 2025)
Furfural dialkyl acetals prepared via acetalization reaction of furfural and alcohols are promising biofuels. Using defined experiments and density functional theory (DFT) simulations, the structure-dependent activity and selectivity for furfural acetalization reaction in the presence of alcohols (methanol, ethanol, propanol and butanol) as solvents was studied over well-defined supported Pd nanostructures (octahedra (111), cubes (100) and spheres (both (111) and (100)). Pd cubes supported over TiO2 in the presence of ethanol as a solvent (at 303 K and balloon pressure H-2) exhibited 78 % conversion and 100 % selectivity for furfural diethyl acetal product in a short time (similar to 180 min). In contrast, Pd octahedra (111) and Pd spheres showed low conversions (18 % and 6 %) at the same reaction conditions. Interestingly, when used as a solvent, methanol showed the highest conversion (90 %) and selectivity (100 %) for furfural acetalization over Pd cubes. DFT simulations provided mechanistic insight into the reactivity of the two different Pd facets (111) and (100) in the presence of alcohol molecules towards furfural acetalization reaction. A three-step reaction mechanism was proposed for furfural acetalization with alcohols: (i) alcohol hydroxyl-dehydrogenation (ii) hydrogenation of furfural carbonyl oxygen, and (iii) formation of hemiacetal product. For all three steps, Pd (100) exhibited low activation barriers (51.6, 26.7 and 76.2 kJ/mol) compared to Pd (111) surface (78.6, 35.8 and 92.2 kJ/mol) in the presence of ethanol. The activation barriers for the above steps were further reduced to 47.8, 23.9 and 64.6 kJ/mol on Pd (100) in the presence of methanol, explaining the experimental high reactivity aided by methanol. DFT calculations elucidated the role of the hydrogen bonding network between the solvent molecules and adsorbate, enabling proton-coupled electron transfer for accelerated reactions.
Keywords: Acetalization; DFT; facet-dependent reactivity; furfural; Furfural dialkyl acetals; solvent effect